Demographic and economic determinants of migration - Nicole B. Simpson (IZA World of Labor, 2022)
There are a myriad of economic and non-economic forces behind the decision to migrate. Migrants can be "pushed" out of their home countries due to deteriorating economic conditions or political unrest. Conversely, migrants are often "pulled" into destinations that offer high wages, good health care, strong educational systems, or linguistic proximity. In making their decision, individuals compare the net benefits of migration to the costs. By better understanding what forces affect specific migrant flows (e.g. demographic characteristics, migrant networks, and economic conditions), policymakers can set policy to target (or reduce) certain types of migrants.
Keywords: F22; J61; O15; 330; migration; determinants; costs; networks